Pengembangan Dimensi Bernalar Kritis dan Berkebhinekaan Global Melalui Proyek Penguatan Profil Pelajar Pancasila - Hajarwati, Inggit Zammi; Heru Prasetiyo, Wibowo (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
This research aims to describe the development of critical thinking and global diversity dimensions in the Strengthening Project of Pancasila Student Profiles at Al-Irsyad Junior High School, Surakarta. A qualitative approach with a descriptive method was used to explore the perspectives and experiences of a selected group of informants through purposive sampling. The informant group consisted of the school principal, civic education teachers, and four students recruited based on criteria supporting data acquisition. The study employed various data collection techniques, including observation, interviews, and documentation, which were analyzed interactively. The results of this research indicate that Al-Irsyad Junior High School has implemented programs, including meaningful learning, as an effort to develop its students. The Strengthening Project of Pancasila Student Profiles is designed with a structured and planned focus on themes, program implementation and its impact. Through the Strengthening Project of Pancasila Student Profiles, the school not only emphasizes academic aspects but also shapes the character of students in critical thinking and an open attitude towards global diversity.